2023
DOI: 10.3389/fonc.2023.1287650
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing oral squamous cell carcinoma prediction: the prognostic power of the worst pattern of invasion and the limited impact of molecular resection margins

Pavel Hurník,
Jana Režnarová,
Zuzana Chyra
et al.

Abstract: ObjectiveOral squamous cell carcinoma (OSCC) originates from the mucosal lining of the oral cavity. Almost half of newly diagnosed cases are classified as advanced stage IV disease, which makes resection difficult. In this study, we investigated the pathological features and mutation profiles of tumor margins in OSCC.MethodsWe performed hierarchical clustering of principal components to identify distinct patterns of tumor growth and their association with patient prognosis. We also used next-generation sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Recent studies showed a correlation of TB – evaluated as a dichotomous or semi-quantitative variable – with the potential of locoregional metastasis in OSCC ( 26 28 ). We assessed similar findings in the investigated cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed a correlation of TB – evaluated as a dichotomous or semi-quantitative variable – with the potential of locoregional metastasis in OSCC ( 26 28 ). We assessed similar findings in the investigated cohort.…”
Section: Discussionmentioning
confidence: 99%